Varietal growth and gains from trade in Indian dairy imports: a quantitative introspection - Bitan Mondal; Smita Sirohi (Agricultural Economics Research Review, 2023)
Indian dairy sector has witnessed a sharp increase in imports of diversified dairy products subsequent upon the economic reforms in the 1990s. The imports of dairy products stemmed from different countries (dairy varieties) surged almost 3 times since then. Also there was a 6-fold increase in the number of product varieties imported. Considering a monopolistic competition framework and applying the constant elasticity of substitution utility function, we find Indian consumers have benefitted about 4% in terms of the total value of output of dairy industry. An exploration of elasticity of substitution at highly disaggregated HS 8-digit level shows that higher imports in product lines having higher elasticity of substitution limit varietal gains to consumers, while import diversification towards less substitutable products like whey-based products (HS 0404) and cheese and curds (HS 0406) enhances gains to consumers.